1997
DOI: 10.1109/49.585771
|View full text |Cite
|
Sign up to set email alerts
|

Quick simulation: a review of importance sampling techniques in communications systems

Abstract: Importance sampling (IS) is a simulation technique which aims to reduce the variance (or other cost function) of a given simulation estimator. In communication systems, this usually, but not always, means attempting to reduce the variance of the bit error rate (BER) estimator. By reducing the variance, IS estimators can achieve a given precision from shorter simulation runs; hence the term "quick simulation." The idea behind IS is that certain values of the input random variables in a simulation have more impa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
158
0
8

Year Published

2002
2002
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 252 publications
(172 citation statements)
references
References 85 publications
2
158
0
8
Order By: Relevance
“…Hence, most samples in stratum 2 will not be propagated in the true system. Such a gain in efficiency is similar to the one achieved by the improved IS method proposed in [13] and known as IS with excision [8].…”
Section: The Coarse/fine Approachsupporting
confidence: 67%
See 2 more Smart Citations
“…Hence, most samples in stratum 2 will not be propagated in the true system. Such a gain in efficiency is similar to the one achieved by the improved IS method proposed in [13] and known as IS with excision [8].…”
Section: The Coarse/fine Approachsupporting
confidence: 67%
“…The idea is based on running an MC estimation after observing an approximate, but usually faster to simulate, description of the system under test, and then to use such information to drive the estimation on the true system. It was shown that our proposed implementation of the method is a new form of adaptive IS, which is similar in spirit to the "excision IS" method [8]. The algorithm showed a significant computational gain compared to standard MC at practical values of to .…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…This conversion is illustrated for one coordinate. The parity patterns present are converted to PAM2 (here, '0 → +1) and mapped to the corresponding channel coefficients as given in (2). The probability counts are extracted from the field associated with each type and normalized by p −1 = 2 k , corresponding to the the total number of possible bit patterns associated with one codeword.…”
Section: Extension To Multiple Codewords and Additional Interferencementioning
confidence: 99%
“…Sample-size reduction methods, such as importance sampling, exist, but long channel memory reduces their effectiveness of due to the dimensionality effect [2]. For channels with long memory, analytically computing the probability distributions associated with received voltages is common practice [3]- [5] but all such simulators assume the transmitted bits to be independent.…”
Section: Introductionmentioning
confidence: 99%